The impact of the COVID-19 pandemic on the practice-oriented education sector and assessment methods - Blinov, Vladimir [Verfasser] (My University, 2022)
„Although the process of digitalization of the intermediate Vocational Education and Training (VET) in Russia began before the COVID-19 pandemic, the usage of distance and blended learning technologies was rare during the crisis. The study identified the main weaknesses of intermediate VET which came to light during the pandemic as well as the barriers to distance learning both for teachers and learners. Therefore, the study emphasises that the problems identified need to be addressed in order to ensure a successful digital transformation process of the intermediate VET.“ (author’s abstract; BIBB-Doku)
Keywords: L 4.2 Mediengestützte Lehr-Lernformen; P 3.2 Lehrpersonal; I 2.2.2 Osteuropa; 370; Berufsbildung; Pandemie; Auswirkung; Digitalisierung; Fernunterricht; Blended learning; Bildungspersonal; Russland